Comparative Effects of Some Botanical Extracts and Chemicals in Controlling the Red Spider Mite Tetranychus evansi Baker & Pritchard on Solanaceous Crops - Azandémè-Hounmalon, G.Y.; Onzo, A.; Adandonon, A.; Houedenou, J.; Djossou, R.; Gnanvossou, D.; Tamò, M. (European Scientific Journal, ESJ, 2022)
The tomato red spider mite, Tetranychus evansi, is an invasive pest reported on solanaceous crops in Benin around 2008, causing heavy economic damage. The control of this mite by farmers is mainly done through intensive applications of chemical pesticides that are not always effective. In the present study, we evaluated in a laboratory, at IITA-Benin, the effects of two botanical insecticides: the Cashew Nut Shell Liquid (CNSL) and Neem oil. This is together with Acarius 18 EC, a chemical acaricide generally used by growers on eggs and adult females T. evansi. The half recommended dose (0.5 l/ha), the recommended dose (1 l/ha), and the double recommended dose (2 l/ha) of Acarius and Neem oil as well as solutions at 1%, 2 %, 3%, 4% and 5% of CNSL were tested. Mean egg hatching rates varied significantly among treatments, ranging from 0.00 ± 0.00% (Neem oil and CNSL) (respectively at half recommended dose and 4%) to 100% (Control). Mortality of adult female T. evansi also differed significantly among treatments (P < 0.0001), ranging from 22.00 ± 4.20% to 100%. The highest mortality rates were recorded with Neem oil at any doses and with CNSL at 4%, whereas the lowest rate was recorded with the control treatment. Fecundity of pesticide-treated females T. evansi and proportion of eggs that hatched revealed significant differences among all doses of products (P < 0.0001). It appears from this study that even the half recommended dose of Neem oil and the CNSL at 4% were very effective on suppressing T. evansi populations and should, therefore, be subject to further studies to test their compatibility with natural enemies, and to determine strategies for their efficient applications in greenhouse and under field conditions.